The price of sin: The effects of social norms on markets - Hong, Harrison; Kacperczyk, Marcin (Journal of financial economics, 2009)
We provide evidence for the effects of social norms on markets by studying “sin” stocks—publicly traded companies involved in producing alcohol, tobacco, and gaming. We hypothesize that there is a societal norm against funding operations that promote vice and that some investors, particularly institutions subject to norms, pay a financial cost in abstaining from these stocks. Consistent with this hypothesis, we find that sin stocks are less held by norm-constrained institutions such as pension plans as compared to mutual or hedge funds that are natural arbitrageurs, and they receive less coverage from analysts than do stocks of otherwise comparable characteristics. Sin stocks also have higher expected returns than otherwise comparable stocks, consistent with them being neglected by norm-constrained investors and facing greater litigation risk heightened by social norms. Evidence from corporate financing decisions and the performance of sin stocks outside the US also suggest that norms affect stock prices and returns.